Subsidies to homeownership and central city rent - Alexander Daminger (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
This paper analyzes the effects of German homeownership subsidies on the intra-city rent structure. Using a large-scale micro data set on German rent offerings, I first construct novel city rent indexes that include various rings around cities' CBDs. Using triple differences (TD) frameworks, I then estimate the introduction of the homeownership subsidies' effects on rent for the cities that received varying subsidy rates. The empirical results indicate that subsidies to homeownership lower central apartment rent premiums in those cities, where they give the "biggest bang for the buck". Consequently, I find that homeownership subsidies contribute to an increase in housing affordability through the price changes in the rental market: an increase in the subsidies leads potential homeowners to move away from the CBD, resulting in a decrease in the rental demand and lowering the rent.
Keywords: H22; H71; R31; R38; 330; homeownership; housing subsidies; homeownership subsidy; triple differences